Fresh agricultural products cold chain logistics distribution and path optimization - Liu, Shiyi; Liu, Li (International Journal of Global Economics and Management, 2024)
Based on the reference to the existing research results, combined with the enterprise’s current distribution path, to minimize the cost as the research objective, to establish the relevant model, and put forward the control of logistics costs, increase the infrastructure investment in cold chain logistics, the optimization of the path of countermeasure proposals, to further improve the efficiency of the enterprise distribution and increase customer satisfaction at the same time reduces the cost of distribution, increase the core competitiveness of the industry.